THE INFLUENCE OF SALES PROMOTION, E-SERVICE QUALITY, REPUTATION CUSTOMER SWITCHING BEHAVIOR TOWARDS E-WALLET IN MANADO DURING PANDEMIC COVID-19 ERA (CASE STUDY: SHOPEEPAY) - Walukow, Tessalonica Miracle; Lapian, S. L. H. V. Joyce; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2024)
Customer Switching Behavior is the freedom for customers to choose a product to use. Customers can still be generous with service providers and can avoid switching when they are given greater value than they would receive when choosing a competitor. This study aims to analyse the influence Sales Promotion, E-Service Quality, and Reputation on Customer Switching Behavior towards E-Wallet in Manado during Pandemic Covid-19 Era (Case Study : Shopeepay). The researcher conducted this research through quantitative methods. Multiple Regression Analysis method is used to analyse the influence of the independent variables toward the dependent variable. Sample were taken from customers who switch usage from other E-Wallets or other payment tools to Shopeepay with a total sample of 100 respondents. The results of this study indicate that Sales Promotion, E-Service Quality has effect on Customer Switching Behavior towards E-Wallet and Reputation has no effect on Customer Switching Behavior towards E-Wallet. The results also indicate that Sales Promotion, E-Service Quality and Reputation simultaneously effect Customer Switching Behavior significantly. Keyword: Sales Promotion, E-Service Quality, Reputation, Customer Switching Behavior